Implementasi Pendekatan Saintifik Dengan Strategi Problem Based Learning Dan Discovery Learning Ditinjau Dari Kemampuan Komunikasi Matematik Siswa Kelas Viii Smp Negeri 1 Teras Tahun Ajaran 2015/2016 - Wulandari, Sistami; , Dra. Nining Setyaningsih, M.Si (2016)
This research aimed to analyze the influence of the scientific approach to the Problem Based Learning strategy and Discovery Learning on learning achievement in terms of mathematical communication. This research was an experimental research to provide treatment of learning strategies. The population in this research, were all students VIII class of 1st Junior High School Teras Village academic year 2015/2016 includes 7 classes. The research sample was determined by random cluster sampling technique, in order to obtain classes VIII B as a experiment class and VIII C as a control class. The research instrument used questionnaire mathematical communication skills and mathematics achievement tests. The collected data were analyzed using anava two pathways that were previously done using methods Liliefors test for normality and homogeneity test using Bartlett method. The results of the study at α = 5% showed that: (1) there was a significant relationship between the use of the approach of scientific strategies Problem Based Learning and Discovery Learning on student achievement, with FA = 12.765, (2) there was a significant effect of communication mathematics to achievement learning, with FB = 4.236, (3) there isn't interaction effect between learning approachment and communication mathematical to student achievement, with FAB = 1.437.